FPOs as a Sustainable Business: Factors impacting performance of Agriculture Collectives in India - Bharti, Nisha; Kumari, Sneha (Zielona Góra: Faculty of Economics and Management Press)
In recent years, the government`s focus on promoting FPOs has led to an increase in FPOs multifold. However, with the fast growth of FPOs, it is important to identify what impacts the performance of FPOs. This study raised the question, "What impacts the performance of FPOs?" This study attempts to identify the measures for the performance of the FPOs.
Keywords: performance measures; collectives; agriculture; farmers; governance; professional management; financial support; farmer producer organization